Corporate governance in China: A modern perspective - Jiang, Fuxiu; Kim, Kenneth A. (Journal of Corporate Finance, 2015)
This paper provides a modern overview of corporate governance in China and in doing so highlights many corporate governance features and issues that are, for the most part, unique to China. We also describe how papers in this special issue advance our understanding of corporate governance in China and in general.